The Place of Women in Environmental Management and Sustainability in Nigeria - Ezugwu, Umezurike J.; Maduka, Enyimba; Etta , Emmanuel E.; Ekanem, Samuel Aloysius; Egaga, Ushie Thomas (Studia Ecologiae et Bioethicae, 2024)
In this essay, we contend that the relationship between human society and physical environment is not gender neutral, as men and women are treated inequitably. There exists an inequitable binary structure between the two polar values, as human society often exploits and degrades the environment, and women are undermined in various occasions. The role of women is undermined in environmental management and monitoring. Our strategy in dealing with this issue of negligence would be to expose the misconception that women have little or nothing to contribute in environmental management beside biological reproductive roles, and activities such as cooking, washing, fetching firewood and nursing of children. We will also show the negative impacts of these forcefully assigned female duties on the climate, and how this leads to pollution, which in turn, obstructs the biospheres (plant and animal species). Using the principle of complementarity, the paper insists on the need to eradicate all socio-culturally perceived superlative attributes of distinction between human society and environment or masculinity and femininity. The paper calls for mainstreaming of gender perspective, expansion of women’s opportunities and participation in environmental management, at all levels, for environmental sustainability.